Legal Protection for Investors in Share Transactions with Repurchase Agreement Rights According to DSN-MUI Fatwa No. 94/DSN-MUI/IV/2014 - Nursandi, Reza; Ardiansyah (Universitas Al-Qolam Malang, 2025)
The DSN-MUI Fatwa No. 94/DSN-MUI/IV/2014 serves as an Islamic legal guideline to ensure that REPO transactions are conducted based on valid, transparent, and fair contracts. This study aims to analyze the forms of legal protection for investors in stock transactions with REPO rights according to the fatwa and review its compliance with the capital market legal system in Indonesia. The research method used is normative juridical with a statutory approach and sharia fatwas. The results show that this fatwa provides strong legal protection for investors through the regulation of the contract structure, the prohibition of transfer of benefits during the REPO period, and dispute resolution provisions that comply with sharia principles. This protection is strengthened by the role of the Financial Services Authority (OJK) and the Sharia Supervisory Board in supervising and implementing sharia REPO transactions. Thus, this fatwa is an important instrument in realizing safe and just sharia capital market transactions.